Debate Education and Management in Malaysia - Mohamad, Nor Asiah (2012)
The focus of the presentation is based on the author's experience as the Secretary for Malaysian Public Higher Learning Institution Debate Council from 2010-2011. The management involves the planning of the academic modules, skills as well as the debate tournament.